Penggunaan Bahasa Pada Anak TK Satu Atap SD Negeri 58 Kota Bengkulu - Lisa Sriwahyuni; Ngudining Rahayu; Irma Diani (UNIB Press, 2026)
Abstract This study aims to describe the use of language in kindergarten children. The method used in this research is descriptive method. The data collection techniques are observation, recording technique, free listening technique, and note taking technique. The data in this study were obtained from the speech of kindergarten children. The data source of this research is kindergarten children of SD Negeri 58 Bengkulu City. The data processing techniques are (1) data transcription, (2) data identification, (3) data classification, (3) data interpretation, and (5) conclusion. Based on the results of research on language use in One Roof Kindergarten children, there are fourteen children, namely in the form of word classes found, there are eight types of words which include nouns, verbs, adjectives, pronomines, numeralia, adverbs, conjunctions, interjections, and sentences. Two children mastered more of the eight word classes, including nouns, verbs, adjectives, pronomina, numeralia, adverbs, conjunctions, interjections, while twelve children only mastered four word classes, namely nouns, verbs, conjunctions, interjections and single sentences, simple sentences, command sentences. Keywords: Language Use, Word Class, Sentence.